2005
DOI: 10.1080/00049158.2005.10674970
|View full text |Cite
|
Sign up to set email alerts
|

A review of eucalypt dieback associated with bell miner habitat in south-eastern Australia

Abstract: SummaryWe aim to assess current knowledge, and identify gaps in knowledge concerning bell-miner-associated dieback (BMAD) in south-eastern Australia. We review BMAD as a form of forest dieback, and bell miner and psyllid interrelations. We then consider indirect and direct causal factors associated with local functional scales (tree crown), and finally, indirect and direct causal factors associated with broader functional scales (forest stand and landscape processes). This paper emphasises published literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Furthermore, the increase in insect abundance in areas where bell miners are present may indicate that a variety of herbivorous insects are responsible for dieback, not only psyllids as previously suggested e.g. [45] [70].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the increase in insect abundance in areas where bell miners are present may indicate that a variety of herbivorous insects are responsible for dieback, not only psyllids as previously suggested e.g. [45] [70].…”
Section: Discussionmentioning
confidence: 88%
“…However, psyllid nymphs, that produce a sugaryprotective coating and feed on the sap of leaves, have been implicated in increased levels of damage in trees, particularly in association with bell miners [12] [44]. This relationship is an extreme example of creating exclusion zones as it has been associated with tree death, known as bell miner associated dieback [11] [45]. Yet, little is known about the top-down effects of bell miners on the insect populations in their territories.…”
Section: Introductionmentioning
confidence: 99%
“…Not every location was sampled in all years, or for the same lengths of time. We studied birds variously from late August to midOctober at Yellowdine in 1997Yellowdine in , 2001Yellowdine in , 2005Yellowdine in -7, and 2010Widgiemooltha 2005-7;Norseman North 2006-8, 2010and, Norseman West 2003, 2005-8, 2010.…”
Section: Study Locationmentioning
confidence: 99%
“…In addition, some species of honeyeaters (Meliphagidae) exclude other birds from the habitats they occupy influencing the composition of avian communities and the distribution of species on a landscape scale (Loyn et al 1983;Grey et al 1998;Wardell-Johnson et al 2005). Such behaviour changes the abundances and kinds of plant-eating arthropods, thereby affecting the health of plants and entire ecosystems (Loyn et al 1983;Grey et al 1998;Wardell-Johnson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Declining stands often develop dense understoreys of a few native or exotic shrubs and decline has sometimes been attributed to reduced water and nutrient status as a result of competition from these "invasive" understoreys [5,6]. However several studies have shown that soil water and nitrogen status is increased in declining stands, and trials of understorey removal have failed to ameliorate declines [7].…”
Section: Invasions In Eucalypt Systemsmentioning
confidence: 99%